Law Enforcement of Illegally Used Clothing Imports and the Protection of Indonesia’s Textile Industry - Fratiwi, Putri Yasmin; Mulyanti, Asti Sri (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study aims to analyze law enforcement against illegal imports of used clothing and to examine the legal protection of the national textile industry based on Law Number 7 of 2014 on Trade. The purpose of this research is to evaluate the effectiveness of the prohibition policy on used clothing imports and to assess its role in safeguarding domestic industrial competitiveness, particularly in the case of Pelita Market, Sukabumi. The research employs a normative juridical method using a statutory approach and a conceptual approach. Legal materials consist of primary, secondary, and tertiary sources collected through library research and analyzed using qualitative descriptive analysis with grammatical and systematic interpretation. The findings indicate that the prohibition of used clothing imports has been clearly regulated under Law Number 7 of 2014 and its implementing regulations, including criminal and administrative sanctions. However, law enforcement remains ineffective due to weak supervision, limited inter-agency coordination, administrative loopholes, and strong market demand. This situation creates unfair business competition and undermines the competitiveness of the national textile industry. In conclusion, strengthening law enforcement mechanisms, improving inter-agency coordination, and implementing consistent supervision are essential to ensure effective protection of the national textile industry and to realize a fair and sustainable trading system.